Chemical composition and anti-oxidant potential on essential oils of Thymus quinquecostatus Celak. from Loess Plateau in China, regulating Nrf2/Keap1 signaling pathway in zebrafish - Ting He (Nature Portfolio, 2020)
Abstract Chemical profile and antioxidant potency of essential oils (EOs) of Thymus quinquecostatus Celak. (thyme oils) obtained from Loess Plateau in China had been studied. 130 constituents of thyme oils were determined using gas chromatography-mass spectrometry (GC–MS) and carvacrol ethyl ether was firstly reported as a new natural product, which has been used as a synthetic flavoring substance with no safety concern. The thyme oils showed the anti-oxidant activity using 2,2 diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azino-bis-(3-ethylbenzothiazoline-6-sulfonate) (ABTS), ferric reducing antioxidant power (FRAP) and thiobarbituric acid reactive substances (TBARS) and conferred protection against oxidative stress in zebrafish. In addition, a class of carvacrol analogues was found to develop as potential natural antioxidant products of thyme oils from Loess Plateau by the correlation analysis. YL-thyme oil performed the best antioxidant activity in this research, which could be recommended as preferred sources of thyme oils. Furthermore, YL-thyme oil exhibited a potent antioxidant capacity by reactive oxygen species (ROS) scavenging, enhancing the endogenous antioxidant system, inhibiting lipid peroxidation and activation of Keap1/Nrf2 pathway in zebrafish.